Sedimentation and erosion patterns within anabranching channels in a lowland river restoration project. Issue 3 (3rd July 2022) - Medel, Ivan D.; Stubblefield, Andrew Phillip; Shea, Conor
ABSTRACT: Anabranching channel designs are seldom utilized for river restoration projects despite their potential for efficient hydraulic conveyance and robust floodplain habitat. We evaluated a stream restoration project that concentrates base flows within a single deep, narrow channel overflowing into secondary channels and an alternating series of higher elevation active benches at flood stages. The design represents an implementation of a Cluer and Thorne SEM Stage 8 anastomosing system aimed at increasing transport efficiency of water and sediment through low gradient river reaches to alleviate flooding on adjacent properties. We investigated the performance of the project's hydraulic conveyance and the general utility of anabranching channels as a restoration alternative by assessing the distribution and magnitude of deposition and erosion response patterns. High-resolution survey indicate aggradation is not occurring within the main channel. Between summer 2016 and summer 2017, reaches experienced mean elevation decreases between 0.08 and 0.29 m indicating effective discharge rates transported dominant grain sizes. Along some reaches, bed scour was sufficient to undercut banks, producing slumps, which may affect long-term conveyance capacities. Lateral bank scour was limited to reaches exposed to daily tidal flows. Variable deposition patterns were observed within secondary channels, depending on cumulative precipitation, dominant hydrology, and channel entrance orientation. Isolated tidal flows resulted in deposition, while long duration flood flows produced intertidal floodplain scour. Within fluvially-dominated benches, uniform longitudinal deposition of fine-grained sediments was associated with low channel entrance flow rates. Higher entrance flow rates resulted in concentrated deposition of coarse-grained particles, up to 0.21 m, and a longitudinal gradient of decreasing sediment sizes and magnitude. This study builds upon previous work by providing a high-resolution assessment of a constructed anabranching channel system and confirms its suitability for efficient hydraulic conveyance within fluvial reaches of lowland rivers and provides general recommendations for future designs.